ROZWÓJ SYSTEMÓW PROGNOZOWANIA INFLACJI W WYBRANYCH KRAJACH - Przybylska-Kapuścińska, Wiesława; Szyszko, Magdalena (Wydział Prawa i Administracji UAM, 2009)
States that use modern monetary policy strategies base their money policy strategy on inter alia, inflation forecasts. When it comes to the decision making regarding the fundamental instrument of monetary policy that needs to take into account the forecasting results, an inflation forecast system is needed. Broadly speaking, the forecasting system comprises not only the method of inflation forecasting, but other aspects as well, including the authorship of the forecast, its type, manner of formulating sentences, frequency of forecast making, or the extent to which this information is publicly disclosed. The paper presents the evolution of inflation forecast systems in five new European Union members - the Czech Republic, Poland, Rumania, the Slovak Republic and Hungary. Those states, all being new market economies, have struggled with similar difficulties and each has developed its own system of coping with inflation forecasts. They often drew on experience of central banks and their long tradition.
DEVELOPMENT OF INFLATION FORECAST SYSTEMS IN SELECTED STATES